THEORETICAL FUNDAMENTALS OF ACCOUNTING POLICY, CHANGES IN ACCOUNT ESTIMATES AND ERRORS WHEN DRAWING UP A FINANCIAL REPORT: https://doi.org/10.5281/zenodo.14759831 - Niyozov , Dilshodjon (Journal of Contemporary World Studies, 2025)
This scientific article analyzes the forms of financial statements in the Republic of Uzbekistan and the importance and tasks of the process of their compilation and presentation. The article will also focus on the system of formation of the financial report, which is carried out on the basis of the "forms of Financial Reporting" approved by the Ministry of Finance of the Republic of Uzbekistan and the financial policy of the Republic of Uzbekistan (CEC), the important requirements for its formation and presentation. The correct and accurate structure of reporting forms, transparency of financial information, audit control and the effectiveness of the accounting system are among the main factors necessary for the development of the economy of Uzbekistan. The compliance of the correct drawing up of financial statements with international standards and its application in the conditions of Uzbekistan and the economic and legal compatibility of this process are covered in detail. This article provides an in-depth analysis of the role of the correct development and presentation of financial reporting forms in the financial system, audit and accounting activities.